2022
DOI: 10.1038/s41541-022-00543-4
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of live-attenuated measles viruses as platform technology for recombinant vaccines

Abstract: Live-attenuated measles virus (MeV) has been extraordinarily effective in preventing measles infections and their often deadly sequelae, accompanied by remarkable safety and stability since their first licensing in 1963. The advent of recombinant DNA technologies, combined with systems to generate infectious negative-strand RNA viruses on the basis of viral genomes encoded on plasmid DNA in the 1990s, paved the way to generate recombinant, vaccine strain-derived MeVs. These live-attenuated vaccine constructs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…One potential concern of using the MMR vaccine platform is the preexisting immunity. Several studies showed that the preexisting MeV immunity had minimal impact on MeV replication and induction of antigen-specific immune responses ( 38 40 ). In phase II trial, rMeV-based Chikungunya virus has excellent immunogenicity in the presence of preexisting MeV immunity ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…One potential concern of using the MMR vaccine platform is the preexisting immunity. Several studies showed that the preexisting MeV immunity had minimal impact on MeV replication and induction of antigen-specific immune responses ( 38 40 ). In phase II trial, rMeV-based Chikungunya virus has excellent immunogenicity in the presence of preexisting MeV immunity ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various platforms have been employed in the development of COVID-19 vaccines [ 200 , 201 ]. Some use traditional approaches, such as inactivated viruses or live-attenuated viruses, which have proven successful in influenza [ 202 ] and measles vaccines [ 203 ], respectively. Other approaches utilize newer platforms, including recombinant proteins [ 204 ] (as seen in human papillomavirus vaccines) and vectors [ 205 ] (utilized in Ebola vaccines).…”
Section: Vaccines and Adverse Reactions After Immunizationmentioning
confidence: 99%